Internet of Things-Based Home Respiratory Muscle Training for Patients with Chronic Obstructive Pulmonary Disease: A Randomized Clinical Trial - Chen Q; Wu X; Huang Y; Chen L (International Journal of COPD, 2024)
Qiong Chen,1,* Xuejuan Wu,1,* Yanjin Huang,2 Lingling Chen1 1Respiratory Medicine Department, Xiamen Haicang Hospital, Xiamen, Fujian, People’s Republic of China; 2Nursing Department, Xiamen Haicang Hospital, Xiamen, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuejuan Wu, Respiratory Medicine Department, Xiamen Haicang Hospital, No. 89 Haiyu Road, Haicang District, Xiamen, Fujian, 361026, People’s Republic of China, Tel +86 150 6070 2657, Email 15060702657@163.comPurpose: Whether Internet of Things (IoT)-based home respiratory muscle training (RMT) benefits patients with comorbid chronic obstructive pulmonary disease (COPD) remains unclear. Therefore, this study aims to evaluate the effectiveness of IoT-based home RMT for patients with COPD.Patients and Methods: Seventy-eight patients with stable COPD were randomly divided into two groups. The control group received routine health education, while the intervention group received IoT-based home RMT (30 inspiratory muscle training [IMT] and 30 expiratory muscle training [EMT] in different respiratory cycles twice daily for 12 consecutive weeks). Assessments took place pre-intervention and 12 weeks post-intervention, including lung function tests, respiratory muscle strength tests, the mMRC dyspnea scale, CAT questionnaires, the HAMA scale, and 6-month COPD-related readmission after intervention.Results: Seventy-four patients with COPD were analyzed (intervention group = 38, control group = 36), and the mean age and FEV1 of the patients were 68.65 ± 7.40 years, 1.21 ± 0.54 L. Compared to those of the control population, the intervention group exhibited higher FEV1/FVC (48.23 ± 10.97 vs 54.32 ± 10.31, p = 0.016), MIP (41.72 ± 7.70 vs 47.82 ± 10.99, p = 0.008), and MEP (42.94 ± 7.85 vs 50.29 ± 15.74, p = 0.013); lower mMRC (2.00 [2.00– 3.00] vs 1.50 [1.00– 2.00], p < 0.001), CAT (17.00 [12.00– 21.75] vs 11.00 [9.00– 13.25], p < 0.001), and HAMA (7.00 [5.00– 9.00] vs 2.00 [1.00– 3.00], p < 0.001) scores; and a lower incidence rate of 6-month readmission (22% vs 5%, p = 0.033).Conclusion: Compared with no intervention, IoT-based home RMT may be a more beneficial intervention for patients with COPD.Keywords: chronic obstructive pulmonary disease, internet of things, respiratory rehabilitation, respiratory muscle training